Category Shift in Novel After You by Jojo Moyes - Riandini; Hilman , Evert H (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
This study aimed to analyze the types of category shifts that can be found in this novel and translated novel. In this study, the translator uses category shifts for several sentences, words, clauses, and phrases, as evidenced by the 100 data the researcher collected. It has been proven that 35 data use the Category Shift technique, and 15 use the Class Shift technique. Furthermore, 25 data using the unit shift technique and 25 data using an intra-system shift in this study also analyzed whether shifting in translation would affect the quality of the translation. The quality of the translation was measured using parameters from Nababan and the obtained results. The use of shifting techniques on the quality of translation, as measured through Nababan's theory, produces an average score on aspects of accurate 3, aspects of accelerable 3, and readable 3.